Total Phenolic Content and Hedonic Quality of Germinated Jack Bean Tempeh at Different Fermentation Times and Packaging Types - Agustia, Friska Citra; Salma, Rafida; Hamidah, Salma Azra; Dewi, Kifayati Rosiyanti; Sanayei, Sanaz (Journal of Agri-Food Science and Technology, 2025)
This study evaluated the interaction effects of different fermentation durations and packaging types on producing the best-germinated jack bean tempeh based on total phenolic content (TPC) and hedonic quality. This study uses a factorial experimental design with a randomized group of 3 × 3 treatments. The factors included fermentation durations (48, 60, and 72 hours) and packaging types (plastic, banana leaves, and teak leaves). There were 9 treatments with 3 replications each. Statistical analysis for TPC was performed using ANOVA, while hedonic quality was analyzed using the Friedman test. If significant effects (p<0.05) were detected, data analysis was continued with DMRT. The best treatment was determined using De Garmo's effectiveness index test. The interaction between fermentation duration and packaging type significantly affected TPC (p=0.045), color quality (p=0.000), aroma (p=0.004), and appearance (p=0.000), but had no significant effect on taste quality (p=0.100). The best treatment was tempeh which had a fermentation duration of 60 hours and used plastic packaging. It contained 0,97 mg GAE/g of phenolic compounds (low) with antioxidant activity IC50 value of 6.951,38 ppm (weak). It had hedonic scores of 3.50 for taste (characteristic of tempeh), 3.20 for aroma (not musty), 3.90 for color (white), and 3.20 for appearance (compact). Based on its TPC and antioxidant activity, it is not sufficiently strong to inhibit oxidative stress. These results can be used as a basis for considering the use of germinated jack beans as an alternative antidiabetic functional food product.